2009
DOI: 10.1111/j.1743-6109.2009.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glycemic Control with Risk of Erectile Dysfunction in Men with Type 2 Diabetes

Abstract: Introduction Improvement in glycemic control is likely to reduce the risk of diabetic complication, while its effect on erectile dysfunction (ED) remains unclear. Aim The aim of this study was to evaluate the association of glycemic control with risk of ED in type 2 diabetics. Methods A self-administered questionnaire containing Sexual Health Inventory for Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 60 publications
(71 reference statements)
8
72
2
3
Order By: Relevance
“…These data suggest a possible benefit of tight glycemic control in the prevention of erectile dysfunction. Our results were also consistent with the results of Lu et al, 16 who evaluated the association of glycemic control with risk of ED in type 2 diabetics. A selfadministered questionnaire was obtained from 792 subjects with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These data suggest a possible benefit of tight glycemic control in the prevention of erectile dysfunction. Our results were also consistent with the results of Lu et al, 16 who evaluated the association of glycemic control with risk of ED in type 2 diabetics. A selfadministered questionnaire was obtained from 792 subjects with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 93%
“…Results obtained were classified as described by Resen et al (1997) 7 as follows: good response, (420); fair response (15)(16)(17)(18)(19)(20); and poor response (o15).…”
Section: Methodsmentioning
confidence: 99%
“…However, the treatment rate for dyslipidemia is low in Taiwan. 40 Even if lipid-lowering agents were used, it often coexisted with HT and DM and therefore, adjustment of HT and DM was supposed to have the same effect as adjusting for dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, for patients aged >60 years, only age and duration of diabetes were independent predictors of severe ED. 20 In patients with diabetes, the severity of ED has been linked to the number of circulating endothelial microparticles. 21 The medications that patients are receiving for treatment of diabetes and their complications may influence ED.…”
Section: Ed Associated With Diabetes Control Complications and Medicmentioning
confidence: 99%
“…19,20 Lu et al conducted a study involving 792 men, of whom 83.6% had some degree of ED, including 43% with serious ED. 20 The study showed that, even after controlling for age and duration of diabetes, there was an association between glycated haemoglobin levels (HbA1c) and ED (OR 1.12, 95% CI 1.01 to 1.25). The authors also performed subgroup analysis to investigate the association between age and severe ED.…”
Section: Ed Associated With Diabetes Control Complications and Medicmentioning
confidence: 99%